Enhancing Bacterial DNA Extraction from Urine Tract Infection using Antibiototics - Hajer Khaldoun Mahmoud Yonis; Wasan Jouma Nayif Saleh; Walla Abd Mhysin Taha; Hibatulla Jmal Shaker Mahmoud; Huda Falah Hassan Majbas (American Journal of Biology and Natural Sciences, 2024)
Optimizing the extraction of Escherichia coli DNA from urine samples while keeping costs low is crucial for research and diagnostic purposes. Urine is a convenient and non-invasive sample for studying the urogenital microbiota and diagnosing sexually transmitted infections. However, challenges like low bacterial DNA quantities, PCR inhibitors, and crystal precipitation at cold temperatures can impede efficient DNA extraction and PCR amplification. To address these issues, researchers explored the effectiveness of adding different, The implementation of penicillin treatment as a method to enhance bacterial DNA extraction showed promising results. Here are the key findings: Concentration Variability: The concentration of penicillin solution used for treating bacterial cultures varied based on experimental conditions. Common concentrations ranged from 50 to 1000 units per milliliter (U/mL) or 0.1 to 10 milligrams per milliliter (mg/mL), with low, moderate, and high concentrations yielding varying degrees of cell wall disruption. Treatment Efficacy: Bacterial cultures treated with penicillin showed increased susceptibility to cell wall disruption, leading to enhanced DNA extraction efficiency. The duration of incubation with penicillin varied depending on factors such as bacterial species and desired level of cell wall weakening. Incubation Conditions: Optimal incubation conditions, including temperature and agitation, were maintained during penicillin treatment to ensure effectiveness. These conditions were adjusted based on the specific requirements of the bacterial species under study. Control Groups: Control groups consisting of untreated bacterial cultures or cultures treated with solvent alone were included in the experimental setup to compare the effectiveness of penicillin treatment. This allowed for the assessment of the specific contribution of penicillin to the enhancement of DNA extraction. DNA Extraction Efficiency: Following penicillin treatment, DNA extraction was performed using standard methods such as phenol-chloroform extraction, silica column-based purification, or commercial DNA extraction kits. The weakened cell walls resulting from penicillin treatment facilitated the release of DNA during the extraction process, leading to improved DNA yield and quality. Further validation involved spiking urine samples with DNA from bacterial isolates, specifically targeting Escherichia coli. Median concentrations of Escherichia coli 16S rRNA gene copies were found to be significantly higher in urine processed with Tris-EDTA, indicating the effectiveness of this method in extracting Escherichia coli DNA. By maximizing bacterial DNA yield from urine, especially targeting Escherichia coli, researchers can achieve more accurate assessments of bacterial populations and enhance the detection of specific bacteria in the genital tract. This approach offers a practical and economical solution for extracting Escherichia coli DNA from urine samples, advancing research and diagnostic capabilities in microbiology.